Zebrafish as a Model Organism to Study Melatonin Mechanisms and Treatments - Southwell, Maura; McRobert, Scott (Current Psychopharmacology, 2016)
Background: Melatonin is an evolutionarily highly conserved molecule. In humans, exogenous melatonin has been shown to entrain cir- cadian rhythms to light dark cycles and act as an antioxidant. Many com- plex brain disorders, such as autism and Alzheimer's disease, are associated with abnormal melatonin production or melatonin metabolism. Exogenous melatonin may serve as a potential treatment to improve sleeping patterns and delay neuronal deterioration. Objective: Here we review the advantages of using zebrafish to study the pharmacology of exogenous melatonin treatments to rescue endogenous melatonin abnormalities. Method: We perform a literature review to describe the human melatonin system, zebrafish melatonin system, zebrafish advantages as a model organism, and melatonin research using zebrafish. Conclusions: Zebrafish is a model organism for genetics, physiology, chronobiology, geron- tology, and pharmacology studies. Future melatonin research can incorporate all of these fields to better understand melatonin mechanisms in wildtype and mutant zebrafish to discov- er new potential treatments. A standardized treatment method for all developmental stages should be established to encourage interdisciplinary work.
Keywords: model organism